Fenomena Ketergantungan Artificial Intellegence dalam Tugas Akademik: Studi terhadap Kepercayaan Diri Mahasiswa : The Phenomenon of Artificial Intelligence Dependence in Academic Assignments: A Study of Student Self-Confidence - Nailatul Magfiroh; Muchamad Suradji; Zuli Dwi Rahmawati (ITScience (Information Technology and Science), 2026)
The development of Artificial Intelligence (AI) in higher education has transformed the way students complete various academic assignments. Technologies such as ChatGPT, Grammarly, and various other AI-based platforms make it easier for students to find information, develop ideas, and improve and organize their writing more clearly. However, the intensive use of AI has also raised concerns about the emergence of student dependence on technology and its implications for academic self-confidence. This study uses a qualitative approach with a phenomenological design to in-depth examine students' experiences utilizing AI technology to complete academic assignments. The study subjects consisted of 10 students in the Islamic Religious Education Study Program at Darul 'Ulum Islamic University in Lamongan. Data collection was conducted through in-depth interviews, direct observation, and documentation. The data obtained were then analyzed using the interactive analysis model proposed by Miles and Huberman. The results show that students perceive AI as a tool that increases efficiency and facilitates the completion of academic assignments. However, intensive use also gives rise to indications of dependence and ambivalence in student self-confidence. AI can increase confidence in assignment results, but it can also raise doubts about academic abilities when students must work without technological assistance. The use of AI in academic assignments provides efficiency benefits, but also builds self-confidence that tends to be conditional and has the potential to affect students' independent thinking.